Airway Telomere Length in Lung Transplant Recipients - Mackintosh, John A.; Yerkovich, Stephanie T.; Tan, Maxine E.; Samson, Luke; Hopkins, Peter MA; Chambers, Daniel C. (Frontiers in Immunology, 2021)
Introduction: Chronic lung allograft dysfunction (CLAD) represents the major impediment to long term survival following lung transplantation. Donor and recipient telomere length have been shown to associate with lung transplant outcomes, including CLAD. In this study we aimed to measure the telomere lengths of bronchial and bronchiolar airway cells in lung allografts early after transplantation and to investigate associations with CLAD and all-cause mortality. Methods: This prospective, longitudinal study was performed at The Prince Charles Hospital, Australia. Airway cells were collected via bronchial and bronchiolar airway brushings at post-transplant bronchoscopies. The relative telomere length in airway cells was determined by quantitative PCR based on the T/S ratio. All patients were censored for CLAD and all-cause mortality in August 2020. Results: In total 231 bronchoscopies incorporating transbronchial brush and bronchial brush were performed in 120 patients. At the time of censoring, 43% and 35% of patients, respectively, had developed CLAD and had died. Airway bronchiolar and bronchial telomere lengths were strongly correlated (r=0.78, p<0.001), confirming conservation of telomere length with airway branch generation. Both the bronchiolar (r = -0.34, p<0.001) and bronchial (r = -0.31, p<0.001) telomere length decreased with age. Shorter airway telomere length was associated with older donor age and higher donor pack-year smoking history. Neither the bronchiolar nor the bronchial airway telomere length were associated with the development of CLAD (HR 0.39 (0.06-2.3), p=0.30; HR 0.66 (0.2-1.7), p=0.39, respectively) or all-cause mortality (HR 0.92 (0.2-4.5), p=0.92; HR 0.47 (0.1-1.9), p=0.28, respectively). Conclusions: In this cohort, airway telomere length was associated with donor age and smoking history but was not associated with the future development of CLAD or all-cause mortality.